Persepsi Penumpang Bus Transjakarta (BUSWAY) Terhadap Tarif Dan Headway - Zulfikri, Zulfikri (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Transjakarta Buswatj is expected to be a mass public transport that can serve the people of Jakartaespecially in reducing the travel time. But aver time, the frequency of buswatj was unable to meet thedemand, causing the accumulation of passengers, especially during peak hours. That problem couldbe avercome btJ increasing the fleet of buses which is the headway can be shortened, but the tariff mustbe increase to rover the operating cost. The analysis of the data indicate that for 57.73% of respondentswilling to use busway rates to Rp 3,500 with 10-minute headway. If the tariff was raised to Rp4,000 with 9 minutes headwm;, only 45.2% of respondents willing to use the busway. In otherwords, respondents were only considering the rates and did not make headwm; and indicate that thepassenger of buswai; is mostly who move from other public transport.Keywords: Transjakarta, busway, headway, tarif